PERBEDAAN PERCEIVED QUALITY DARI MILLENIALS YOGYAKARTA TERHADAP KOMPAS TV DAN KOMPAS.COM SEBAGAI MEDIA BERITA - Immanuel Dwi Asmoro Tunggal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
In a marketing, perceived quality holds an important role. If what consumer perceived about the product is same with the quality of product itself, that is it can affect the level of consumer satisfaction when they consume a product / service. As well in the news industry, perceived quality also affects reader satisfaction and inturn they will reread through the media. Kompas, as one of media industry in Indonesia now also using some channel to spread its information through television channel called Kompas TV and online channel called Kompas.com. Each channel has its advantages and disadvantages as a news channel. This study tries to compare the perceived quality of millennials generation in Yogyakarta toward these two channels in packaging their news. Thus study uses a survey method by asking 100 respondents. The result of this study show that Kompas TV is perceived better than Kompas.com. Mean value of Kompas TV is 34.63 > 34.16 for mean value of Kompas.com. Kompas TV is perceived as media which can provide visual evidence better than Kompas.com with mean value of Kompas TV is 3.30 > 3.14 for Kompas.com meanwhile, Kompas.com is perceived as a channel which can provide variety of viewpoints in each news report with mean value is 3.06 > 2.99 Kompas TV.